Design and Analysis of a Plate Heat Exchanger in the View of Performance Improvement and Cost Reduction - H. Jamshak, S; Dev Anand, M; B. Akshay, S; Arun, S; Prajeev, J; Prabhakaran, Prajeesh (International Journal of Engineering and Technology, 2018)
Redesigning of a system is a modification of existing system for reducing the disadvantages over the system and improves the features for getting more output that are desired. For redesigning the existing conventional heat exchanger by the new designed heat exchanger. Conventional heat exchanger has a major disadvantage consuming more space, high cost and maintenance is difficult. Plate heat exchanger has a major advantage over a conventional heat exchanger are that the liquid are exposed to main larger surface area because the liquids spread out over the plate. It is a specialized design well suited to transferring heat between low pressure liquids. The plate produces an extremely large surface area which allows for the fasten possible transfer and studying the plate material, gasket material, chevron angle, and surface enlargement angle. Design a plate heat exchanger by according more advantages and evaluate the cost of newly designed heat exchanger and compared to existing heat exchangers and validate the designs by flow analysis.Â Â